Secondary battery and preparation method and device thereof
By using dry process to prepare single-sided electrode sheets in the laminated battery cells of lithium-ion secondary batteries, and introducing a surface layer with a dielectric constant of 2.6 to 10 in the separator, the problems of increasing thickness and mass of electrode sheets, poor electrolyte infiltration effect, long liquid injection time, and high battery impedance in the prior art are solved, and efficient and economical battery performance improvement is achieved.
Patent Information
- Application Number
- CN202311747052.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-18
- Publication Date
- 2025-06-20
AI Technical Summary
In the laminated battery cells of existing lithium-ion secondary batteries, the positive electrode sheet and the negative electrode sheet are both coated on both sides, resulting in excess coating of the outermost negative electrode sheet, increasing the thickness and quality of the battery cell. At the same time, it is difficult to prepare a single-sided coated electrode sheet with good quality in wet coating process, and the secondary batteries of dry electrode have problems such as poor electrolyte infiltration effect, long liquid injection time, and high battery impedance.
A dry electrode film is used in the laminated battery cell by using a dry process. By attaching the dry electrode film to both sides or one side of the current collector, a single-sided electrode sheet is formed, and a hot press composite molding is used to solve the problem that it is difficult to prepare a single-sided electrode sheet in the wet process. In addition, a surface layer with a dielectric constant of 2.6 to 10 is introduced into the separator to improve the lyophilicity of the electrolyte and reduce the liquid injection time and impedance of the battery.
The single-sided electrode sheet prepared by the dry process has high compaction density and ductility, which solves the problem of increasing thickness and mass of the electrode sheet. At the same time, it improves the electrolyte infiltration performance of the battery, reduces the liquid injection time and impedance of the battery, improves the processing matching, electrical performance and reduces the cost of the battery.
Smart Images

Figure BDA0004615680370000141 
Figure BDA0004615680370000142 
Figure BDA0004615680370000151
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a secondary battery and a method and device for preparing the same. Background Art
[0002] The assembly of lithium-ion secondary batteries usually refers to the process of assembling the positive and negative pole pieces, separators, tabs, shells and other components into a battery. The assembly is mainly divided into two types: winding type and stacking type. Stacking usually involves stacking the positive and negative pole pieces and separators in the order of positive pole piece-separator-negative pole piece layer by layer to form a stacked cell. Conventional stacked cells are formed by alternating positive and negative pole pieces coated on both sides to form a stacked structure.
[0003] However, current secondary batteries and methods and devices for preparing the same still need to be improved. Summary of the invention
[0004] The inventors found that in the current laminated battery cells, both the positive and negative pole pieces are coated on both sides. The negative pole pieces are on the outermost surfaces on both sides of the battery cell. The negative electrode coating facing the air side (or the battery cell shell side) is redundant and does not participate in the electrochemical process or provide energy. Instead, it increases the thickness and quality of the battery cell. If the outermost negative pole piece is replaced with a single-sided coating, however, the current wet coating process cannot produce a single-sided coated pole piece with good quality. The difficulty lies in the shrinkage of the pole piece after drying and the deformation of the pole piece after rolling. Therefore, removing the excess coating on the outermost pole piece of the laminated battery cell is a problem that plagues the battery cell process. In addition, secondary batteries using dry electrodes have problems such as poor electrolyte infiltration effect, long injection time, and high battery impedance. In view of the shortcomings of the prior art, this application applies the dry process to the laminated battery cell. Two dry electrode films (self-supporting films) can be attached to both sides of the current collector, or one dry electrode film can be attached to one side of the current collector to form a single-sided electrode sheet, thereby solving the problem that the wet process cannot prepare a single-sided electrode sheet. In addition, a surface layer with a dielectric constant of 2.6 to 10 is introduced into the diaphragm. The diaphragm has good lyophilicity to the battery electrolyte, which can improve the wetting performance and reduce the battery injection time, thereby reducing the battery impedance.
[0005] The present application provides a secondary battery, which includes: a stacked structure including N layers of structures formed by alternately stacking a positive electrode sheet and a negative electrode sheet, where N is an integer greater than or equal to 3; along the direction of alternate stacking, the first layer and the Nth layer are first negative electrode sheets, and the negative electrode sheets in the 2nd layer to the (N - 1)th layer are second negative electrode sheets; a separator disposed between adjacent positive electrode sheets and negative electrode sheets; wherein, the first negative electrode sheet includes a first current collector and a first dry electrode film disposed on one side of the first current collector, the second negative electrode sheet includes a second current collector and second dry electrode films disposed on opposite sides of the second current collector, the positive electrode sheet includes a third current collector and third dry electrode films disposed on opposite sides of the third current collector, and the first dry electrode film faces the adjacent separator; the separator includes a base film and surface layers disposed on opposite sides of the base film, and the dielectric constant of the surface layer is 2.6 to 10.
[0006] The present application also provides a method for manufacturing a secondary battery, which includes: providing a stacked structure precursor including N layers of structures formed by alternately stacking a positive electrode sheet and a negative electrode sheet, where N is an integer greater than or equal to 3; along the direction of alternate stacking, the first layer and the Nth layer are first negative electrode sheets, and the negative electrode sheets in the 2nd layer to the (N - 1)th layer are second negative electrode sheets; the first negative electrode sheet includes a first current collector and a first dry electrode film disposed on one side of the first current collector, the second negative electrode sheet includes a second current collector and second dry electrode films disposed on opposite sides of the second current collector, the positive electrode sheet includes a third current collector and third dry electrode films disposed on opposite sides of the third current collector, and the first dry electrode film faces the adjacent separator; a separator is disposed between adjacent positive electrode sheets and negative electrode sheets, the separator includes a base film and surface layers disposed on opposite sides of the base film, and the dielectric constant of the surface layer is 2.6 to 10; performing a first hot pressing treatment on the stacked structure precursor to obtain an electric core.
[0007] The present application also provides a device, which includes the secondary battery described above or the secondary battery obtained by the manufacturing method described above.
[0008] The beneficial effects of the present application are as follows:
[0009] On the one hand, the present application applies the dry process to the laminated battery cell. Two dry electrode films (self-supporting films) can be attached to both sides of the current collector, or one dry electrode film can be attached to one side of the current collector to form a single-sided electrode sheet. Moreover, the electrode sheet of the present application forms the dry electrode film (dry process self-supporting film) and the current collector by hot pressing and compounding. The dry electrode film itself also has a relatively high compaction density and good ductility. Thus, the problem that it is difficult to prepare a single-sided electrode sheet by the wet process is solved. On the other hand, in the laminated battery cell of the present application, the separator includes a surface layer with a dielectric constant of 2.6 to 10. Thus, for the separator formed by the surface layer within this dielectric constant range, its liquid affinity for the battery electrolyte is good, the infiltration performance is improved, the liquid injection time of the battery is reduced, and thus the battery impedance (DCR) is reduced. Thus, based on the above improvements, the secondary battery of the present application has at least one of the following advantages: excellent processing compatibility, good electrical performance, and lower cost. Detailed Embodiments
[0010] For the sake of brevity, the present application specifically discloses only some numerical ranges. However, any lower limit can be combined with any upper limit to form a range not explicitly recited; and any lower limit can be combined with other lower limits to form a range not explicitly recited. Similarly, any upper limit can be combined with any other upper limit to form a range not explicitly recited. In addition, each individually disclosed point or single numerical value itself can be used as a lower limit or an upper limit and combined with any other point or single numerical value or combined with other lower limits or upper limits to form a range not explicitly recited.
[0011] Unless otherwise specified, the terms used in the present application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in the present application can be measured by various commonly used measurement methods in the art (for example, they can be tested according to the methods given in the embodiments of the present application).
[0012] The list of items connected by the terms "at least one of", "at least one in", "at least one kind in" or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A can include a single component or multiple components. Item B can include a single component or multiple components. Item C can include a single component or multiple components.
[0013] The term "dry electrode film" refers to an electrode film combined with a binder matrix structure that is sufficient to support the film and maintain its shape, enabling the electrode film to be independent without any external support elements such as current collectors. For example, in the absence of other support elements, the dry electrode film can have sufficient strength to be rolled up, processed, and unrolled during the manufacturing process of electrode sheets.
[0014] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and not to limit the scope of the present application.
[0015] I. Secondary battery
[0016] The present application provides a secondary battery, which includes: a laminated structure and a separator. The laminated structure includes an N-layer structure in which positive electrode sheets and negative electrode sheets are alternately laminated, where N is an integer greater than or equal to 3; along the direction of alternate lamination, the first layer and the Nth layer are the first negative electrode sheets, and the negative electrode sheets in the second layer to the N-1th layer are the second negative electrode sheets; the separator is disposed between adjacent positive electrode sheets and negative electrode sheets; wherein, the first negative electrode sheet includes a first current collector and a first dry electrode film disposed on one side of the first current collector, the second negative electrode sheet includes a second current collector and second dry electrode films disposed on opposite sides of the second current collector, the positive electrode sheet includes a third current collector and third dry electrode films disposed on opposite sides of the third current collector, and the first dry electrode film faces the adjacent separator; the separator includes a base film and surface layers disposed on opposite sides of the base film, and the dielectric constant (Dk) of the surface layer is 2.6 to 10.
[0017] On the one hand, the present application applies the dry process to the laminated battery cell. Two dry electrode films (self-supporting films) can be attached to both sides of the current collector, or one dry electrode film can be attached to one side of the current collector to form a single-sided electrode sheet. Moreover, the electrode sheets of the present application form the dry electrode film (dry process self-supporting film) and the current collector by hot pressing and compounding. The dry electrode film itself also has a high compaction density and good ductility. Thus, the problem that it is difficult to prepare a single-sided electrode sheet by the wet process is solved. On the other hand, in the laminated battery cell of the present application, the separator includes surface layers with a dielectric constant of 2.6 to 10. Thus, the separator formed by the surface layers within this dielectric constant range has good liquid affinity for the battery electrolyte, improves the wetting performance, reduces the liquid injection time of the battery, and thereby reduces the battery impedance (DCR), that is, alleviates the problems of poor electrolyte wetting effect, long liquid injection time, and high battery impedance in secondary batteries using dry electrode films. Thus, based on the above improvements, the secondary battery of the present application has at least one of the following advantages: excellent processing compatibility, good electrical performance, and lower cost.
[0018] In some embodiments, the dielectric constant of the surface layer is 2.6 to 10. In some embodiments, the dielectric constant of the surface layer is 2.6, 2.7, 2.8, 2.9, 3, 4, 5, 6, 7, 8, 9, 10 or any value therebetween. Thus, for the separator formed by the surface layer within this dielectric constant range, it has good wettability to the battery electrolyte, improves the wetting performance, reduces the liquid injection time of the battery, and thereby reduces the battery impedance (DCR). If the dielectric constant of the surface layer is too low, the wetting speed will be slow and the liquid injection time will be long.
[0019] In some embodiments, the base film includes at least one of polyethylene, polypropylene, and a polypropylene / polyethylene / polypropylene three-layer film. The surface layer includes a first polymer, or includes a first polymer and an inorganic material, wherein the first polymer includes at least one of polyvinylidene fluoride, polyimide, polyphenylene sulfide, polyacrylate, carboxymethyl cellulose, polyacrylonitrile, polyether ether ketone, polyether ketone ketone, and polychlorotrifluoroethylene; the inorganic material includes at least one of aluminum oxide, hydrated aluminum hydroxide, boehmite, lithium lanthanum titanate (LLTO), and lithium aluminum titanium phosphate (LATP).
[0020] In some embodiments, the tap density of the first dry electrode film is A g / cm 3 , and the tap density of the second dry electrode film is B g / cm 3 , and the tap density of the third dry electrode film is C g / cm 3 , where A < B < C. In the present application, the tap density of the dry electrode film can be adjusted according to the characteristics of the selected active material by conventional technical means in the art, such as controlling the pole piece rolling pressure, rolling temperature, rolling speed, etc., to obtain the desired tap density.
[0021] In some embodiments, 1.3 ≤ A ≤ 1.5. In some embodiments, A is 1.3, 1.35, 1.4, 1.45, 1.5 or any value therebetween. In some embodiments, 1.4 ≤ B ≤ 1.65. In some embodiments, B is 1.4, 1.45, 1.5, 1.55, 1.6, 1.65 or any value therebetween. In some embodiments, 2.2 ≤ C ≤ 3.7. In some embodiments, C is 2.2, 2.3, 2.5, 3, 3.5, 3.7 or any value therebetween. Thus, if the tap density of the dry electrode film is too high, the film will be too brittle to be wound and stored, and the ion transport impedance will be too large; if the tap density of the dry electrode film is too low, the strength will be insufficient for self-support, the conductivity will be too low, and the volumetric energy density of the battery will be too low.
[0022] In some embodiments, the elongation rates of the first dry electrode film, the second dry electrode film, and the third dry electrode film are Z%, where Z ≤ 4. In some embodiments, Z is 0.1, 0.2, 0.7, 1.0, 1.2, 1.5, 1.7, 2, 2.5, 3, 3.5, 4.0, or any value therebetween. Thus, if the rolling elongation rate of the dry electrode film is too high or too low, the active material will be separated from the current collector.
[0023] In some embodiments, the first dry electrode film and the second dry electrode film include a negative electrode active material and a first binder, and the third dry electrode film includes a positive electrode active material and a second binder. The positive electrode active material includes at least one of a lithium nickel transition metal oxide and a phosphate.
[0024] In some embodiments, the negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium. Among them, the silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound, and a silicon carbide compound; the carbon-based material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, carbon nanotubes, and graphene; the tin-based material includes at least one of tin, a tin oxide, and a tin alloy; and the phosphorus-based material includes phosphorus and / or a phosphorus complex. In some embodiments, the negative electrode active material includes a carbon-based material and a silicon-based material. In some embodiments, the silicon-based material includes at least one of a silicon oxide compound and a silicon carbide compound, and the carbon-based material includes at least one of artificial graphite and natural graphite. In some embodiments, the negative electrode active material includes at least one of artificial graphite and natural graphite.
[0025] In some embodiments, the lithium nickel transition metal oxide includes LiNi x Co y M (1-x-y)At least one of O2, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 < x + y ≤ 1. In some embodiments, x is 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or any value therebetween. In some embodiments, y is 0.1, 0.2, 0.3, 0.4, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or any value therebetween. In some embodiments, the lithium nickel transition metal oxide includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide and lithium nickel manganese oxide. In some embodiments, the lithium nickel transition metal oxide includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92 or Ni95.
[0026] In some embodiments, the phosphate includes LiMn k B (1-k) PO4, 0 ≤ k ≤ 1, B includes at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead. In some embodiments, k is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or any value therebetween. In some embodiments, the phosphate includes at least one of lithium iron phosphate and lithium manganese iron phosphate. In some embodiments, the phosphate includes LiMn 0.6 Fe 0.4 PO4 and LiMn 0.8 Fe 0.2 PO4.
[0027] In some embodiments, based on the mass of the first dry electrode film, the mass percentage of the negative electrode active material is 94.5% - 99%, and the mass percentage of the first binder is 0.5% - 2.5%. In some embodiments, based on the mass of the first dry electrode film, the mass percentage of the negative electrode active material is 94.5%, 95%, 96%, 97%, 98%, 99% or any value therebetween, and the mass percentage of the first binder is 0.5%, 0.7%, 0.9%, 1%, 1.5%, 2%, 2.5% or any value therebetween.
[0028] In some embodiments, based on the mass of the second dry electrode film, the mass percentage of the negative electrode active material is 94.5% to 99%, and the mass percentage of the first binder is 0.5% to 2.5%. In some embodiments, based on the mass of the second dry electrode film, the mass percentage of the negative electrode active material is 94.5%, 95%, 96%, 97%, 98%, 99% or any value therebetween, and the mass percentage of the first binder is 0.5%, 0.7%, 0.9%, 1%, 1.5%, 2%, 2.5% or any value therebetween.
[0029] In some embodiments, based on the mass of the third dry electrode film, the mass percentage of the positive electrode active material is 94.5% to 99%, and the mass percentage of the second binder is 0.5% to 3%. In some embodiments, based on the mass of the third dry electrode film, the mass percentage of the positive electrode active material is 94.5%, 95%, 96%, 97%, 98%, 99% or any value therebetween, and the mass percentage of the second binder is 0.5%, 0.7%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3% or any value therebetween.
[0030] In some embodiments, the first binder and the second binder include at least one of polytetrafluoroethylene, polyacrylic acid, polyacrylate, polyvinylidene fluoride, polyurethane, polyamide, polyimide, polyethylene oxide, polyvinyl chloride, polyester, polyether, polyphenylene sulfide, polysulfone, polyacrylonitrile, polyether ether ketone, polyether ketone ketone, ethylene-vinyl acetate copolymer, nitrile rubber, butadiene-styrene copolymer, polyaniline, polythiophene, polypyrrole, poly(phenylene vinylene) and polyacetylene.
[0031] In some embodiments, the first dry electrode film, the second dry electrode film and the third dry electrode film further include a first conductive agent, and the first conductive agent includes at least one of carbon nanotubes, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, graphene and carbon fiber. In some embodiments, based on the mass of the first dry electrode film, the mass percentage of the first conductive agent is 0.5% to 6%. In some embodiments, based on the mass of the first dry electrode film, the mass percentage of the first conductive agent is 0.5%, 1%, 2%, 3%, 4%, 5%, 6% or any value therebetween. In some embodiments, based on the mass of the second dry electrode film, the mass percentage of the first conductive agent is 0.5% to 3%. In some embodiments, based on the mass of the second dry electrode film, the mass percentage of the first conductive agent is 0.5%, 1%, 2%, 3% or any value therebetween. In some embodiments, based on the mass of the third dry electrode film, the mass percentage of the first conductive agent is 0.5% to 3%. In some embodiments, based on the mass of the third dry electrode film, the mass percentage of the first conductive agent is 0.5%, 1%, 2%, 3% or any value therebetween.
[0032] In some embodiments, the thickness of the first dry electrode film is 50 μm to 150 μm. In some embodiments, the thickness of the first dry electrode film is 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, or any value therebetween.
[0033] In some embodiments, the thickness of the second dry electrode film is 50 μm to 150 μm. In some embodiments, the thickness of the second dry electrode film is 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, or any value therebetween.
[0034] In some embodiments, the thickness of the third dry electrode film is 70 μm to 170 μm. In some embodiments, the thickness of the third dry electrode film is 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, or any value therebetween.
[0035] In some embodiments, the first dry electrode film, the second dry electrode film, and the third dry electrode film do not contain detectable processing solvents, processing solvent residues, or processing solvent impurities.
[0036] In some embodiments, the first current collector and the second current collector include at least one of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, and copper-plated composite current collectors. The polymer in the copper-plated composite current collector may be a polymer material such as polypropylene (PP), polyethylene terephthalate (PET), or polyimide (PI).
[0037] In some embodiments, the third current collector includes at least one of aluminum foil, aluminum alloy, stainless steel foil, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, and aluminum-plated composite current collectors. The polymer in the aluminum-plated composite current collector may be a polymer material such as polypropylene (PP), polyethylene terephthalate (PET), or polyimide (PI).
[0038] In some embodiments, the thickness of the first current collector and the second current collector is 4 μm to 12 μm. In some embodiments, the thickness of the first current collector and the second current collector is 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or any value therebetween.
[0039] In some embodiments, the thickness of the third current collector is 8 μm to 15 μm. In some embodiments, the thickness of the third current collector is 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or any value therebetween.
[0040] In some embodiments, a carbon layer is provided on the surfaces of the first current collector, the second current collector, and the third current collector. The carbon layer includes at least one of carbon nanotubes, carbon black, acetylene black, Ketjen black, and graphene. In some embodiments, the thickness of the carbon layer is 0.5 μm to 8 μm. In some embodiments, the thickness of the carbon layer is 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or any value therebetween. In some embodiments, the carbon layer further includes a carbon layer binder, and the carbon layer binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid and its copolymers, polyacrylate, sodium carboxymethyl cellulose, and polyacrylonitrile. In some embodiments, based on the mass of the carbon layer, the mass percentage of the carbon layer binder is 5% to 45%. In some embodiments, based on the mass of the carbon layer, the mass percentage of the carbon layer binder is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or any value therebetween. In some embodiments, the carbon layer is provided between the current collector and the dry electrode film. Thus, providing the carbon layer can reduce the impedance (DCR) of the secondary battery and improve the cycle life of the secondary battery.
[0041] II. Preparation Method of Secondary Battery
[0042] The present application also provides a preparation method of a secondary battery. The secondary battery prepared by this method can be the secondary battery described above, and thus can have all the features and advantages of the secondary battery described above. In some embodiments, the method includes:
[0043] S100: Provide a stacked structure precursor, the stacked structure precursor including an N-layer structure in which a positive electrode sheet and a negative electrode sheet are alternately stacked, N being an integer greater than or equal to 3; along the direction of alternate stacking, the first layer and the Nth layer are the first negative electrode sheets, and the negative electrode sheets in the second layer to the N - 1th layer are the second negative electrode sheets; the first negative electrode sheet includes a first current collector and a first dry electrode film provided on one side of the first current collector, the second negative electrode sheet includes a second current collector and second dry electrode films provided on opposite sides of the second current collector, the positive electrode sheet includes a third current collector and third dry electrode films provided on opposite sides of the third current collector, the first dry electrode film faces the adjacent separator; a separator is provided between adjacent positive electrode sheets and negative electrode sheets, the separator including a base film and surface layers provided on opposite sides of the base film, and the dielectric constant of the surface layer is 2.6 to 10;
[0044] S200: Perform a first hot pressing treatment on the precursor of the laminated structure to obtain an electric cell.
[0045] In some embodiments, the pressure of the first hot pressing treatment is 0.25 MPa to 12 MPa. In some embodiments, the pressure of the first hot pressing treatment is 0.25 MPa, 0.5 MPa, 1 MPa, 2 MPa, 4 MPa, 6 MPa, 8 MPa, 10 MPa, 11 MPa, 12 MPa, or any value therebetween. In some embodiments, the temperature of the hot pressing treatment is 70 °C to 110 °C. In some embodiments, the roller surface temperature is 70 °C, 80 °C, 90 °C, 100 °C, 110 °C, or any value therebetween.
[0046] In some embodiments, the first negative electrode sheet includes a first current collector and a first dry electrode film disposed on one side of the first current collector, the second negative electrode sheet includes a second current collector and second dry electrode films disposed on opposite sides of the second current collector, the positive electrode sheet includes a third current collector and third dry electrode films disposed on opposite sides of the third current collector, and the first dry electrode film faces the adjacent separator.
[0047] In some embodiments, the first dry electrode film is formed on the surface of the first current collector through a second hot pressing treatment to obtain the first negative electrode sheet; the second dry electrode films are formed on opposite sides of the second current collector through a third hot pressing treatment to obtain the second negative electrode sheet; and the third dry electrode films are formed on opposite sides of the third current collector through a fourth hot pressing treatment to obtain the positive electrode sheet.
[0048] In some embodiments, the nip line pressure of the second hot pressing treatment is 0.01 t / cm to 0.5 t / cm, and the nip line pressures of the third hot pressing treatment and the fourth hot pressing treatment are 0.1 t / cm to 5 t / cm. In some embodiments, the nip line pressure of the second hot pressing treatment is 0.01 t / cm, 0.05 t / cm, 0.1 t / cm, 0.15 t / cm, 0.2 t / cm, 0.25 t / cm, 0.3 t / cm, 0.35 t / cm, 0.4 t / cm, 0.45 t / cm, 0.5 t / cm, or any value therebetween. In some embodiments, the nip line pressures of the third hot pressing treatment and the fourth hot pressing treatment are 0.1 t / cm, 0.5 t / cm, 1 / cm, 2 t / cm, 3 t / cm, 4 t / cm, 5 t / cm, or any value therebetween.
[0049] In some embodiments, the roller surface temperatures of the second hot pressing treatment, the third hot pressing treatment, and the fourth hot pressing treatment are 80 °C to 150 °C. In some embodiments, the roller surface temperature is 80 °C, 90 °C, 100 °C, 110 °C, 120 °C, 130 °C, 140 °C, 150 °C, or any value therebetween.
[0050] In some embodiments, the first dry electrode film, the second dry electrode film, and the third dry electrode film are formed through the following steps: mixing and processing an active material and a binder to form a first mixture, subjecting the first mixture to shearing treatment to form a second mixture, and subjecting the second mixture to roll pressing treatment to obtain a dry electrode film. Among them, the first dry electrode film and the second dry electrode film include a negative electrode active material and a first binder, and the third dry electrode film includes a positive electrode active material and a second binder. The negative electrode active material, the first binder, the positive electrode active material, and the second binder have been described above and will not be elaborated here.
[0051] In some embodiments, the linear velocity of the shearing treatment is 10 m / s to 80 m / s, and the shearing temperature is 30°C to 120°C. In some embodiments, the linear velocity of the shearing treatment is 10 m / s, 20 m / s, 30 m / s, 40 m / s, 50 m / s, 60 m / s, 70 m / s, 80 m / s, or any value therebetween, and the shearing temperature is 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or any value therebetween.
[0052] In some embodiments, the linear pressure between rolls of the roll pressing treatment is 0.02 t / cm to 2 t / cm, the roll surface temperature is 30°C to 180°C, and the roll gap is greater than or equal to 20% of the thickness of the dry electrode film. In some embodiments, the linear pressure between rolls of the roll pressing treatment is 0.02 t / cm, 0.05 t / cm, 0.1 t / cm, 0.2 t / cm, 0.4 t / cm, 0.5 t / cm, 0.6 t / cm, 0.8 t / cm, 1 t / cm, 1.2 t / cm, 1.4 t / cm, 1.6 t / cm, 1.8 t / cm, 2 t / cm, or any value therebetween, and the roll surface temperature is 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 140°C, 160°C, 180°C, or any value therebetween.
[0053] In some embodiments, the preparation methods of the first dry electrode film, the second dry electrode film, the third dry electrode film, the first hot pressing treatment, the second hot pressing treatment, the third hot pressing treatment, and the fourth hot pressing treatment do not use solvents. That is to say, the dry electrode film and the hot pressing treatment process do not contain detectable processing solvents, processing solvent residues, or processing solvent impurities.
[0054] In some embodiments, the secondary battery or the secondary battery obtained by the above preparation method further includes an electrolyte. The electrolyte includes a lithium salt, an organic solvent, and an additive.
[0055] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonate, lithium (trifluoromethylsulfonyl)(perfluorobutanesulfonyl)imide (LiFNFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium bis(fluoromalonate)borate (LiBFMB), lithium bis(oxalato)borate (LiBOB), lithium difluoro(oxalato)borate (LiDFOB), lithium difluorodioxalate phosphate, and lithium 4,5-dicyano-2-(trifluoromethyl)imidazole (LiTDI).
[0056] In some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium salt is 4% to 25%. In some embodiments, the mass percentage of the lithium salt is 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value therebetween. In some embodiments, the mass percentage of the lithium salt is 6% to 18%.
[0057] In some embodiments, the organic solvent includes at least one of a linear carbonate and a cyclic carbonate. In some embodiments, the linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, and fluorinated linear carbonate. In some embodiments, the cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate, and butylene carbonate. In some embodiments, the organic solvent further includes a non-fluorinated carboxylic acid ester, and the non-fluorinated carboxylic acid ester is selected from at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone.
[0058] In some embodiments, based on the mass of the electrolyte, the mass percentage of the organic solvent is 40% to 80%. In some embodiments, the mass percentage of the solvent is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In some embodiments, the mass percentage of the solvent is 50% to 70%.
[0059] In some embodiments, the additive includes at least one of vinylene carbonate (VC), ethylene vinylene carbonate, tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), succinonitrile, adiponitrile, glutaronitrile, and hexane trinitrile. In some embodiments, the additive further includes at least one of methyl methanedisulfonate (MMDS), ethyl ethanedisulfonate, 1,3-propane sultone (1,3-PS), 1-propene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), divinyl sulfate (DTD), ethyl methyl sulfate (PCS), ethyl ethyl sulfate (PES), ethyl propyl sulfate (PEGLST), propylene sulfate (TS), ethylenesulfite (DTO), dimethyl sulfite (DMS), and diethyl sulfite (DES).
[0060] In some embodiments, based on the mass of the electrolyte, the mass percentage of the additive is 0.05% to 10%. In some embodiments, the mass percentage of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage of the additive is 0.1% to 5%.
[0061] In some embodiments, the method for preparing a secondary battery includes providing an electrode assembly, injecting electrolyte, encapsulating, and forming. In some embodiments, the temperature for forming is 40°C to 50°C, such as 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, or 49°C.
[0062] In some embodiments, forming includes: charging at a current of 0.05C to 4.25V and standing for 60 min at a temperature of 40°C to 50°C, such as 45°C, a pressure of 150 kgf to 250 kgf, such as 210 kgf, then charging at 0.1C to 4.25V, and then discharging at 0.2C to 3.0V.
[0063] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0064] In some embodiments, the secondary battery may include an outer package, and the outer package can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery can also be a soft package, such as a pouch soft package. The material of the soft package can be a plastic, such as one or several of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0065] In some embodiments, the shape of the secondary battery is not particularly limited and can be cylindrical, square, or any other shape.
[0066] In some embodiments, the present application also provides a battery module. The battery module includes the above-mentioned secondary battery. Since the battery module of the present application adopts the above-mentioned secondary battery, it has at least the same advantages as the secondary battery. The number of secondary batteries included in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0067] In some embodiments, the present application also provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0068] III. Device
[0069] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module, and battery pack. Thus, the device can have all the features and advantages of the secondary battery, battery module, or battery pack described above, which will not be elaborated here.
[0070] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, energy storage systems, etc. To meet the device's requirements for high power and high energy density of the secondary battery, a battery pack or battery module can be used.
[0071] In some other embodiments, the device can be a mobile phone, a tablet computer, a laptop computer, etc. Such a device usually requires being thin and light, and a secondary battery can be used as the power source.
[0072] Examples and Comparative Examples
[0073] Example 1
[0074] Preparation method of dry-process positive electrode sheet:
[0075] The positive electrode active material LiFePO4 (LFP) and the conductive agent Super-P (conductive carbon black) are mixed, and the binder PTFE (polytetrafluoroethylene) particles are added and uniformly mixed. The weight ratio of LFP, Super-P, and PTFE is 96:1.5:2.5. The obtained mixture is subjected to high-speed shearing, controlling the shear linear velocity to be 40 m / s, the shear temperature to be 60 °C, and the shear time to be 18 min to achieve the purpose of PTFE fibrillation. The fibrillated mixture is subjected to hot roll pressing, with the roll surface temperature of 60 °C and the linear pressure of 0.5 t / cm, to obtain a self-supporting electrode film (dry electrode film). The obtained dry electrode film is hot-pressed with a current collector (aluminum foil), with the linear pressure between the rolls being 0.5 t / cm and the roll surface temperature being set to 120 °C to prepare a dry-process positive electrode plate (the dry electrode film is double-sided).
[0076] Preparation method of dry-process negative electrode plate:
[0077] The negative electrode active material graphite (Gr) and the conductive agent Super-P (conductive carbon black) are mixed, and the binder PTFE (polytetrafluoroethylene) particles are added and uniformly mixed. The weight ratio of graphite, Super-P, and PTFE is 96:2:2. The obtained mixture is subjected to high-speed shearing, controlling the shear linear velocity to be 40 m / s, the shear temperature to be 60 °C, and the shear time to be 18 min to achieve the purpose of PTFE fibrillation. The fibrillated mixture is subjected to hot roll pressing, with the roll surface temperature of 60 °C and the linear pressure of 0.5 t / cm, to obtain a self-supporting electrode film (dry electrode film). The obtained dry electrode film is hot-pressed with a current collector, with the linear pressure between the rolls being 0.05 t / cm, the roll surface temperature being set to 120 °C, and the linear pressure between the rolls being set to 0.08 t / cm to prepare a dry-process negative electrode plate. Among them, the dry electrode film in the first negative electrode plate is single-sided, and the dry electrode film in the second negative electrode plate is double-sided.
[0078] Preparation of electrolyte: In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), the lithium salt LiPF6 is fully dissolved in a mixed solution of EC / DEC / EMC (ethylene carbonate / diethyl carbonate / ethyl methyl carbonate) = 25 / 20 / 55 to prepare a 1 mol / L solution, and after stirring evenly, the electrolyte is obtained.
[0079] Separator: PE-based membrane, and the surface layer coated on both sides is a polyimide layer (PI).
[0080] Preparation of Lithium-Ion Secondary Battery: The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked layer by layer in sequence. The separator is placed between the positive electrode sheet and the negative electrode sheet. The first layer and the Nth layer are the first negative electrode sheets (the dry electrode film is single-sided), and the negative electrode sheets from the second layer to the (N - 1)th layer are the second negative electrode sheets (the dry electrode film is double-sided), obtaining a bare battery cell. The bare battery cell is placed in a punched aluminum-plastic film soft package shell, and the prepared electrolyte is injected after sufficient drying. The theoretical battery capacity is 200 mAh. After the battery is stored at 45 °C for 48 h, formed, and secondarily sealed, conventional grading is carried out.
[0081] Examples 2 - 6
[0082] In Examples 2 - 6, other steps are the same as those in Example 1. The differences are that the types of active materials, compaction densities of the first negative electrode sheet, the second negative electrode sheet, and the positive electrode sheet, the thickness of the base film in the separator, the materials of the surface layer, its thickness, and dielectric constant are different, as shown in Table 1 specifically.
[0083] Comparative Examples 1 - 6
[0084] In Comparative Example 1, other steps are the same as those in Example 1. The differences are that the types of active materials, compaction densities of the first negative electrode sheet, the second negative electrode sheet, and the positive electrode sheet, the thickness of the base film in the separator, the materials of the surface layer, its thickness, and dielectric constant are different, as shown in Table 1 specifically. Among them, in Comparative Examples 1 - 4, the separator is a 12 - μm PE base film without a surface layer set, and the dielectric constant shown in Comparative Examples 1 - 4 is actually the dielectric constant of the base film. Among them, in Comparative Examples 5 - 6, the first negative electrode sheet is also set to be double-sided, that is, the first layer and the Nth layer on the outermost side of the formed laminated battery cell are negative electrode sheets with dry electrode films double-sidedly set.
[0085] Testing Method
[0086] 1. Testing of the Compaction Density of Electrode Sheets
[0087] The compaction density of the electrode sheet = the single-sided surface density of the electrode sheet (g / cm 2) / Thickness of one side (cm). Among them, the areal density of the electrode: Cut a piece of the electrode, weigh its mass and record it as M1. Then scrape off the active material layer on the electrode, weigh its mass and record it as M2, and measure the area of the electrode and record it as V. When the active material layer is coated on one side of the electrode, scrape off the active material layer on one side of the electrode. The areal density of one side of the electrode = (M1 - M2) / V, and the thickness of one side of the active material layer is the total thickness of the electrode minus the thickness of the current collector; when the active material layer is coated on both sides of the electrode, scrape off the active material layer on both sides of the electrode. The areal density of one side of the electrode = (M1 - M2) / 2V, and the thickness of one side of the active material layer is the total thickness of the electrode minus the thickness of the current collector first, and then divided by 2. Among them, the mass can be weighed by a standard balance, and the thickness can be measured by a micrometer. When the electrode is a positive electrode, the active material layer is a positive active material layer, and the active material is a positive active material; when the electrode is a negative electrode, the active material layer is a negative active material layer, and the active material is a negative active material.
[0088] 2. Impedance test
[0089] Discharge the lithium-ion battery at a constant current of 1C to 2.5V at 25 ± 2°C, then charge it at a constant current of 0.5C to 4.2V, charge it at a constant voltage of 4.2V to 0.05C, and then discharge it at a constant current of 1C to 50% SOC. Let it stand for 60 minutes, record the voltage U1 after the standing ends, then discharge it at a constant current of 2C for 10s, record the voltage U2 after the discharge ends, record the 2C current as I, and let it stand for 60 minutes. Calculate the discharge DCR (impedance) of the battery at 50% SOC according to the formula DCR = (U1 - U2) / I.
[0090] 3. Test method for rolling elongation
[0091] Take the dry-process electrode film and the current collector, with a length of 100 - 1000mm. The lengths of the dry-process electrode film and the current collector are L0 and L1, and the thicknesses of the dry-process electrode film and the current collector are t0 and t1; set a constant rolling gap t2, with an upper limit of the rolling pressure of 2000N / cm; the rolling linear speed is 1m / min; measure the length L2 of the dry-process electrode film after being pressed. Among them: L1 > L0 + 10; t2 = t0 / 2 + t1; the rolling elongation = (L1 - L0) / L0 * 100%.
[0092] 4. Test method for dielectric constant
[0093] Use a dielectric constant tester, stack 10 layers of the separator, and test to obtain the dielectric constant value ε1. If the separator has a surface layer, use tape to remove the surface layer of each layer, and record the thicknesses d1 and d2 of the separator before and after peeling, and then test the dielectric constant ε2 again. The dielectric constant of the surface layer is:
[0094]
[0095] 5. First Coulomb efficiency test
[0096] Under the condition of 25 °C, the prepared lithium-ion secondary battery is charged at a constant current of 1C to 4.2V, and then charged at a constant voltage until the current is less than 0.05C, and the initial charge capacity is recorded. After standing for 5 minutes, it is discharged at a rate of 1C to 2.5V, and the initial discharge capacity is recorded. The first Coulomb efficiency performance test of the lithium-ion secondary battery = initial discharge capacity / initial charge capacity × 100%.
[0097] Test results
[0098] Table 1
[0099]
[0100] Table 2
[0101]
[0102] It can be seen from Examples 1 to 6 and Comparative Examples 1 to 4 that the dry process of the present application is applied to the laminated battery cell, and a dry electrode film can be attached to one side of the current collector to form a single-sided electrode sheet. On the one hand, when the dry process of the present application is applied to the laminated battery cell, two dry electrode films (self-supporting films) can be attached to both sides of the current collector, or a dry electrode film can be attached to one side of the current collector to form a single-sided electrode sheet. Moreover, the electrode sheet of the present application forms the dry electrode film (dry process self-supporting film) and the current collector by hot pressing and compounding. The dry electrode film itself also has a high compaction density and good ductility. Thus, the problem that it is difficult to prepare a single-sided electrode sheet by the wet process is solved. On the other hand, in the laminated battery cell of the present application, the separator includes a surface layer with a dielectric constant of 2.6 to 10. Thus, the separator formed by the surface layer within this dielectric constant range has good lyophilicity to the battery electrolyte, improves the wetting performance, reduces the liquid injection time of the battery, and thus reduces the battery impedance (DCR). That is, it alleviates the problems of poor electrolyte wetting effect, long liquid injection time, and high battery impedance in the secondary battery using the dry electrode film.
[0103] It can be seen from Examples 1 to 6 and Comparative Examples 1 to 4 that no surface layer is provided in Comparative Examples 1 to 4, and the dielectric constant shown in Comparative Examples 1 to 4 is actually the dielectric constant of the base film. Thus, the separator in Comparative Examples 1 to 4 has poor lyophilicity and wetting performance to the battery electrolyte, the liquid injection time of the battery is long, resulting in a decrease in the first Coulomb efficiency and an increase in the battery impedance (DCR).
[0104] As can be seen from Examples 1 to 6 and Comparative Examples 5 to 6, the first negative electrode tab in Comparative Examples 5 to 6 is also set to be double-sided, that is, the first layer and the Nth layer on the outermost side of the stacked battery cell formed are negative electrode tabs with dry electrode films on both sides. The dry electrode film facing the air side (or the battery cell casing side) is redundant and does not participate in the electrochemical process or provide energy. Instead, it increases the thickness and mass of the battery cell, and thus the volumetric energy density is low.
[0105] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those of ordinary skill in the art will recognize that some modifications and changes can be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A secondary battery, characterized in that, Comprising: A laminated structure, which includes an N-layer structure formed by alternately laminating a positive electrode plate and a negative electrode plate, where N is an integer greater than or equal to 3; Along the direction of alternate lamination, the first layer and the Nth layer are the first negative electrode plates, and the negative electrode plates in the second layer to the (N - 1)th layer are the second negative electrode plates; A separator, which is disposed between adjacent positive electrode plates and negative electrode plates; Wherein, the first negative electrode plate includes a first current collector and a first dry electrode film disposed on one side of the first current collector, the second negative electrode plate includes a second current collector and second dry electrode films disposed on opposite sides of the second current collector, the positive electrode plate includes a third current collector and third dry electrode films disposed on opposite sides of the third current collector, and the first dry electrode film faces the adjacent separator; The separator includes a base film and surface layers disposed on opposite sides of the base film, and the dielectric constant of the surface layer is 2.6 to 10.
2. The secondary battery according to claim 1, characterized in that, The base film includes at least one of polyethylene, polypropylene, and a polypropylene / polyethylene / polypropylene three-layer film; and / or The surface layer includes a first polymer, or includes a first polymer and an inorganic material. Among them, the first polymer includes at least one of polyvinylidene fluoride, polyimide, polyphenylene sulfide, polyacrylate, carboxymethyl cellulose, polyacrylonitrile, polyether ether ketone, polyether ketone ketone, and polychlorotrifluoroethylene; the inorganic material includes at least one of alumina, hydrated aluminum hydroxide, boehmite, lithium lanthanum titanate, and lithium titanium aluminum phosphate.
3. The secondary battery according to claim 1 or 2, characterized in that, The tap density of the first dry electrode film is Ag / cm 3 , the tap density of the second dry electrode film is B g / cm 3 , the tap density of the third dry electrode film is C g / cm 3 , the secondary battery satisfies at least one of the following conditions: (1) A < B < C; (2)1.3≤A≤1.5; (3)1.4≤B≤1.65; (4)2.2≤C≤3.7。 4. The secondary battery according to claim 3, characterized in that, The elongation rates of the first dry electrode film, the second dry electrode film, and the third dry electrode film are Z%, and Z ≤ 4.
5. The secondary battery according to claim 4, characterized in that, The first dry electrode film and the second dry electrode film include a negative electrode active material and a first binder, the third dry electrode film includes a positive electrode active material and a second binder, and the positive electrode active material includes at least one of lithium nickel transition metal oxides and phosphates.
6. The secondary battery according to claim 5, characterized in that, The lithium nickel transition metal oxide includes LiNi x Co y M (1-x-y) at least one of O2, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 < x + y ≤ 1; and / or The phosphate includes LiMn k B (1-k) at least one of PO4, 0≤k≤1, B includes at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead; and / or The negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium. Among them, the silicon-based material includes at least one of silicon, silicon alloy, silicon oxide compound, and silicon carbide compound; the carbon-based material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, carbon nanotubes, and graphene; the tin-based material includes at least one of tin, tin oxide, and tin alloy; the phosphorus-based material includes phosphorus and / or a phosphorus complex; and / or Based on the mass of the first dry electrode film, the mass percentage of the negative electrode active material is 94.5% to 99%, and the mass percentage of the first binder is 0.5% to 2.5%; and / or Based on the mass of the second dry electrode film, the mass percentage of the negative electrode active material is 94.5% to 99%, and the mass percentage of the first binder is 0.5% to 2.5%; and / or Based on the mass of the third dry electrode film, the mass percentage of the positive electrode active material is 94% to 99%, and the mass percentage of the second binder is 0.5% to 3%; and / or The first binder and the second binder include at least one of polytetrafluoroethylene, polyacrylic acid, polyacrylate, polyvinylidene fluoride, polyurethane, polyamide, polyimide, polyethylene oxide, polyvinyl chloride, polyester, polyether, polyphenylene sulfide, polysulfone, polyacrylonitrile, polyetheretherketone, polyetherketoneketone, ethylene-vinyl acetate copolymer, nitrile rubber, butadiene-styrene copolymer, polyaniline, polythiophene, polypyrrole, polyethylene, polypropylene, polyvinylpyrrolidone, poly(phenylene vinylene), and polyacetylene; and / or The first dry electrode film, the second dry electrode film, and the third dry electrode film further include a first conductive agent, and the first conductive agent includes at least one of carbon nanotubes, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, graphene, and carbon fiber; based on the mass of the first dry electrode film, the mass percentage of the first conductive agent in the first dry electrode film is 0.5% to 3%; based on the mass of the second dry electrode film, the mass percentage of the first conductive agent in the second dry electrode film is 0.5% to 3%; based on the mass of the third dry electrode film, the mass percentage of the first conductive agent in the third dry electrode film is 0.5% to 6%; and / or The thickness of the first dry electrode film is 50 μm to 150 μm; and / or The thickness of the second dry electrode film is 50 μm to 150 μm; and / or The thickness of the third dry electrode film is 70 μm to 170 μm; and / or The first dry electrode film, the second dry electrode film, and the third dry electrode film do not contain detectable processing solvents, processing solvent residues, or processing solvent impurities.
7. The secondary battery according to claim 1 or 2, characterized in that, The first current collector and the second current collector include at least one of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, and copper-coated composite current collector; and / or The third current collector includes at least one of aluminum foil, aluminum alloy, stainless steel foil, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, and aluminum-coated composite current collector; and / or The thickness of the first current collector and the second current collector is 4 μm to 12 μm; and / or The thickness of the third current collector is 8 μm to 15 μm; and / or A carbon layer is provided on the surfaces of the first current collector, the second current collector, and the third current collector. The carbon layer includes at least one of carbon nanotubes, carbon black, acetylene black, Ketjen black, and graphene, and the thickness of the carbon layer is 0.5 μm to 8 μm.
8. A method for preparing a secondary battery, characterized in that,Including: Providing a stacked structure precursor, the stacked structure precursor includes an N-layer structure in which a positive electrode sheet and a negative electrode sheet are alternately stacked, and N is an integer greater than or equal to 3; Along the alternating stacking direction, the first layer and the Nth layer are the first negative electrode sheets, and the negative electrode sheets in the second layer to the (N - 1)th layer are the second negative electrode sheets; the first negative electrode sheet includes a first current collector and a first dry electrode film disposed on one side of the first current collector, the second negative electrode sheet includes a second current collector and second dry electrode films disposed on opposite sides of the second current collector, the positive electrode sheet includes a third current collector and third dry electrode films disposed on opposite sides of the third current collector, and the first dry electrode film faces the adjacent separator; a separator is disposed between the adjacent positive electrode sheet and the negative electrode sheet, and the separator includes a base film and surface layers disposed on opposite sides of the base film, and the dielectric constant of the surface layer is 2.6 to 10; Perform a first hot pressing treatment on the precursor of the laminated structure to obtain an electric cell.
9. According to the preparation method described in claim 8, characterized in that, The pressure of the first hot pressing treatment is 0.25 MPa to 12 MPa, and the temperature is 70 °C to 110 °C; and / or Form the first dry electrode film on the surface of the first current collector through a second hot pressing treatment to obtain the first negative electrode sheet; form the second dry electrode films on opposite sides of the second current collector through a third hot pressing treatment to obtain the second negative electrode sheet; form the third dry electrode films on opposite sides of the third current collector through a fourth hot pressing treatment to obtain the positive electrode sheet; wherein, the nip line pressure of the second hot pressing treatment is 0.01 t / cm to 0.5 t / cm; the nip line pressures of the third hot pressing treatment and the fourth hot pressing treatment are 0.1 t / cm to 5 t / cm; and / or The preparation methods of the first dry electrode film, the second dry electrode film, and the third dry electrode film, and the steps of the first hot pressing treatment, the second hot pressing treatment, the third hot pressing treatment, and the fourth hot pressing treatment do not use solvents.
10. A device, characterized in that, Include the secondary battery according to any one of claims 1 to 7 or the secondary battery obtained by the preparation method according to any one of claims 8 to 9.